Genomic landscape of complete Acinetobacter phages: clustering, core-shell genes, and synteny insights - Pang, Sean Jia Le; Wee, Soon Keong; Yap, Eric Peng Huat (Frontiers in Microbiology, 2026)
IntroductionAcinetobacter baumannii is a major clinical threat due to its multidrug resistance and frequent involvement in nosocomial outbreaks. Bacteriophage therapy offers a targeted alternative, but its success depends on a deep understanding of phage genomics and proteomics. This study aims to cluster the current database of Acinetobacter phages, identify phage clusters with potential for therapeutic applications and highlight proteins that may be valuable for phage engineering.MethodsA total of 250 publicly available complete Acinetobacter phage genomes were downloaded from NCBI database. The genomes were grouped into clusters using PhamClust. A phylogenetic tree using the terminase large subunit and the portal protein was charted. Gene synteny analysis was conducted using Clinker, while the protein family output from PhaMMseqs was utilized to investigate both broadly conserved and cluster-specific phams.ResultsAcinetobacter phages were classified into 12 clusters, including the newly identified cluster 10. While the terminase large subunit and portal protein proved useful for cluster-level grouping, they were insufficient for resolving finer phylogenetic relationships. Three conserved enzymes, endolysins, a DNA helicase, and an HNH homing endonuclease, were found across multiple clusters, alongside a diverse array of cluster-specific phams.DiscussionCluster 10 was found to contain three phages with exceptionally broad host ranges, highlighting its strong potential for therapeutic development. Additionally, the three conserved enzymes shared across multiple clusters, especially the endolysins, may serve as valuable tools for phage engineering due to their broad conservation. The cluster-specific phams offer biological insights and may also form the basis for developing cluster-specific primers or molecular diagnostics. Collectively, these findings deepen our understanding of Acinetobacter phage diversity and point toward new avenues for advancing phage-based therapies and diagnostics.